Specialized microbiomes facilitate natural rhizosphere microbiome interactions counteracting high salinity stress in plants - Santos, Susana Silva; Rask, Klara Andrés; Vestergård, Mette; Johansen, Jesper Liengaard; Priemé, Anders; Frøslev, Tobias Guldberg; González, Ana M. Martín; He, Huan; Ekelund, Flemming (Environmental and experimental botany, 2021)
•Specialized microbiome transfers increased plant growth at higher salinities.•Rice field microbiome is better suited to support plant growth.•Halotolerant microbiome promoted similar network structures between salinities.•Plant growth at high salinities was linked to denser and more complex networks.•Potential keystone taxa tolerant to salinity were identified. The root microbiota is crucial for plant productivity and stress tolerance. Still, our understanding of the factors that structure these microbial communities is limited, and we lack a theoretical framework to predict their assemblage and interactions. Here, we used rice as a model system to explore the hypothesis that microbiomes from specific environments enhance plant tolerance to salinity. We used 16S rRNA sequencing to track salinity-induced changes in microbiomes of plants inoculated with either a rice field microbiome, or a halotolerant microbiome, compared to only the seed microbiome. We found that, at salinities higher than 1.1 % plant growth was severely impeded. Nevertheless, at 0.11 % and 0.35 % salinity, plants inoculated with rice field and halotolerant microbiomes displayed enhanced shoot and root biomass, when compared to plants surviving only with the seed microbiome. Rice field microbiome had the highest plant growth-promoting effect and was the only treatment that promoted growth at 0.35 % salinity. The salinity effects on bacterial composition and alpha diversity were more pronounced for plants that relied only on the seed microbiome. The root-associated compartments harboured distinct microbiomes, but salinity explained most of the variation observed. Rice plants interacted with the rice field and halotolerant microbiomes to shape rhizosphere microbial community composition and the co-occurrence patterns, supporting plant growth at higher salinity. Assemblages of the halotolerant microbiome promoted similar network structures between the different salinity treatments, when compared to the other inoculations. Moreover, salinity responsive and keystone bacteria were taxonomically diverse and responded in guilds of taxa to the salinity levels. We conclude that both specialized inoculations differ greatly in how they influence the plant microbiome and that plant growth at higher salinity levels was associated with a denser and more complex root microbial community.